Role of heparan sulfate proteoglycans in optic disc and stalk morphogenesis. Issue 10 (6th May 2014) - Cai, Zhigang; Grobe, Kay; Zhang, Xin; Mansour, Suzanne L.; Ornitz, David M.
<x xml:space="preserve">Abstract</x> Background: Heparan sulfate proteoglycans (HSPG) are important for embryonic development by means of the regulation of gradient formation and signaling of multiple growth factors and morphogens. Previous studies have shown that Bmp/Shh/Fgf signaling are required for the regionalization of the optic vesicle (OV) and for the closure of the optic fissure (OF), the disturbance of which underlie ocular anomalies such as microphthalmia, coloboma, and optic nerve hypoplasia. Results:To study HSPG‐dependent coordination of these signaling pathways during mammalian visual system development, we have generated a series of OV‐specific mutations in the heparan sulfate (HS) N‐sulfotransferase genes (Ndst1 and Ndst2) and HS O‐sulfotransferase genes (Hs2st, Hs6st1, and Hs6st2) in mice. Of interest, the resulting HS undersulfation still allowed for normal retinal neurogenesis and optic fissure closure, but led to defective optic disc and stalk development. The adult mutant animals further developed optic nerve aplasia/hypoplasia and displayed retinal degeneration. We observed that MAPK/ERK signaling was down‐regulated in Ndst mutants, and consistent with this, HS‐related optic nerve morphogenesis defects in mutant mice could partially be rescued by constitutive Kras activation. Conclusions: These results suggest that HSPGs, depending on their HS sulfation pattern, regulate multiple signaling pathways in optic disc and stalk morphogenesis. Developmental Dynamics 243:1310–1316, 2014. © 2014 Wiley Periodicals, Inc.